2008
DOI: 10.1093/carcin/bgn248
|View full text |Cite
|
Sign up to set email alerts
|

Oral nicotinamide protects against ultraviolet radiation-induced immunosuppression in humans

Abstract: Cutaneous immunity, which is a key defence against the development of skin cancers, is suppressed by even small doses of ultraviolet (UV) radiation. Preventing this UV-induced immunosuppression may therefore reduce the incidence of skin cancer. Nicotinamide (vitamin B3) has immune-protective and cancer-preventive effects against UV radiation in mice, and we have shown previously that topical nicotinamide is immune protective in humans. Using the Mantoux model of skin immunity in healthy volunteers, we compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
123
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(127 citation statements)
references
References 36 publications
2
123
0
2
Order By: Relevance
“…Using the Mantoux model of delayed-type hypersensitivity (DTH) in healthy volunteers, we have shown that nicotinamide protects from UV-induced immunosuppression in humans [63, 64]. 5% topical nicotinamide, applied 15 minutes before or after each of 3 daily exposures to low-dose solar-simulated (ss) UV (equivalent to less than ~8 minutes exposure to Sydney spring sunlight [65]), prevented UV-induced suppression of Mantoux reactions [63].…”
Section: Nicotinamide: Photoimmunosuppression and Skin Cancermentioning
confidence: 99%
“…Using the Mantoux model of delayed-type hypersensitivity (DTH) in healthy volunteers, we have shown that nicotinamide protects from UV-induced immunosuppression in humans [63, 64]. 5% topical nicotinamide, applied 15 minutes before or after each of 3 daily exposures to low-dose solar-simulated (ss) UV (equivalent to less than ~8 minutes exposure to Sydney spring sunlight [65]), prevented UV-induced suppression of Mantoux reactions [63].…”
Section: Nicotinamide: Photoimmunosuppression and Skin Cancermentioning
confidence: 99%
“…Nicotinamide enhances DNA repair in UVirradiated human HaCaT keratinocytes and ex vivo human skin (7), likely by preventing UV-induced ATP depletion (8). The immunosuppressive effects of UV radiation are also reduced by nicotinamide (9,10). In phase 2 clinical trials, it reduced premalignant actinic keratoses and significantly reduced new non-melanoma skin cancers, although this was not a primary endpoint (11).…”
Section: Introductionmentioning
confidence: 99%
“…Nicotinamide, an inhibitor of SIRT1, plays an essential role in many cellular processes such as increasing DNA replication, modulating mitochondrial quantity and quality, and reducing ultraviolet radiation-induced immunosuppression (Jang, Kang, & Hwang, 2012;Sandler & Andersson, 1988;Yiasemides, Sivapirabu, Halliday, Park, & Damian, 2009). It is an inexpensive and non-toxic compound and currently used for a variety of skin ailment applications.…”
Section: Discussionmentioning
confidence: 99%